Energy Efficient Homes: Appliances in General - Hyun-Jeong Lee; Kathleen C. Ruppert; Wendell A. Porter; Travis Prescott (EDIS, 2008)
FCS-3266, a 4-page fact sheet by Hyun-Jeong Lee, Kathleen C. Ruppert, Wendell A. Porter, and Travis Prescott, is part of the Energy Efficient Homes series. It describes what you should look for in energy efficient home appliances, and other energy saving tips. Includes references. Published by the UF Department of Family, Youth and Community Sciences, June 2008.